Về một thuật toán chặt khúc chuỗi thời gian thành các đoạn tự hồi quy AR(p) - Quỳnh, Nguyễn Hồ; Hòa, Nguyễn Trung (Journal of Computer Science and Cybernetics, 2016)
The problem of segmentationing time series is treated. The segments are considered as autoregressive models. The segmentation is based in the differency of the partiel autocorrelative function. A numeral result by Monte-Carlo simulation has been proposed in order to interprete the efficiency of the algorithm.